2016
DOI: 10.1088/0031-9155/61/20/7263
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution iterative reconstruction in high-resolution extremity cone-beam CT

Abstract: Application of model-based iterative reconstruction (MBIR) to high resolution cone-beam CT (CBCT) is computationally challenging because of the very fine discretization (voxel size <100 µm) of the reconstructed volume. Moreover, standard MBIR techniques require that the complete transaxial support for the acquired projections is reconstructed, thus precluding acceleration by restricting the reconstruction to a region-of-interest. To reduce the computational burden of high resolution MBIR, we propose a multires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…46,47 Highresolution cone-beam CT systems with voxel size <100 mm for assessment of bone and joint health are under development. 48 We have demonstrated that morphological analysis of the joint space performed on CT images with sufficiently high resolution is pertinent to describe indirectly tibial cartilage and meniscal impairments. The parameters JS_min, JS_asym, and JS_ent are the most interesting to characterize OA, and JS_asym despite a low reproducibility is a good predictor of the cartilage thickness.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Highresolution cone-beam CT systems with voxel size <100 mm for assessment of bone and joint health are under development. 48 We have demonstrated that morphological analysis of the joint space performed on CT images with sufficiently high resolution is pertinent to describe indirectly tibial cartilage and meniscal impairments. The parameters JS_min, JS_asym, and JS_ent are the most interesting to characterize OA, and JS_asym despite a low reproducibility is a good predictor of the cartilage thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Other CT methods, including conventional CT with a voxel size < 0.6 mm and cone beam CT, would have provided greater accuracy but were not available in our teaching hospital. High-resolution cone beam CT images have slices as thin as 0.1 mm combined with low radiation, relative to slice thickness and radiation for conventional CT. 29,30 The distal portion of the radius is a common site of limb-sparing surgery in companion animals 31 and a site of hemiarthroplasty in humans. 32 Accurate assessment of the geometry of joint surfaces is a prerequisite for optimization of articulating custom orthopedic implants (eg, custom arthroplasties or hemiarthroplasties).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting boundary between the fine and coarse regions is outside the cranium (in air, presumably not of diagnostic interest), so downsampling / upsampling voxels in the other region is not considered when calculating neighboring voxel differences in the subsequent image reconstruction. In the current work, we investigate an implementation specifically with two voxel sizes (coarse and fine), but the term “multi-resolution” (c.f., “dual resolution”) is used for consistency with previous work (Delaney and Bresler 1995, Cao et al 2016) and for generality in anticipation of future work in which voxel size is more continuously varied from a fine value in the SFOV to progressively coarser values outside the SFOV.…”
Section: Methodsmentioning
confidence: 99%
“…In the regularization part, taking the fine region as an example, K F is the number of neighboring voxels in the fine region, and Ḣ and ω are the gradients and curvatures of the Huber penalty function H , respectively. While the pseudocode in (Cao et al 2016) used a small detector pixel size for the projection of a high-resolution region-of-interest and a large detector pixel size for the rest of the projection data, the pseudocode here used a single detector pixel size.…”
Section: Methodsmentioning
confidence: 99%